ASM503: Personnel administration and management / Faculty of Business Management - UiTM, Faculty of Business Management (2021)
This course examines the role of administrative office manager’s role in managing people and human resource activities effectively. It provides an understanding of workforce trends, laws affecting human resource management, and job analysis. In addition, the course covers the important role in managing people and human resource, specifically recruitment and the selection process, as well as employee orientation, training & development, appraisals and compensation.